Director's Success, Studio's Failure. - McDONALD, NEIL (Quadrant Magazine)
The article discusses about "Blackhat", a 2015 American Hollywood blockbuster directed by Michael Mann. The film is about a hacker who has access to the computer systems with some wrong intent but this film had failed as it has not come up with the expectations of the audience and due to this it was not released in Australia. Mann, during the film had hired real computer hackers who had trained the cast in order to present the role of the characters authentic.